Factors determining initial trust amongst Malaysian online shoppers - Doraisamy, Logama (2012)
Enhancing the level of trust by consumers on e-commerce will reduce perceived uncertainty and fears and this will be an effective way to lure consumers to online transactions. The starting point of trust building is the initial trust, since consumers’ perception of risk and security is most salient in an unfamiliar web setting and attracting consumers depends on the extent of initial trust engendered by vendors, and persuading consumers to transact with them in the future, depends on the extent of improvement of initial trust (McKnight,Choudhury and Kacmar, 2002). Whilst there are many factors that contribute to the growth of online shopping, the physiological factor of trust plays a significant role for successful closing of an online businesses especially amongst the first time buyers, i.e. development of initial trust. Due to the significance of initial trust in different context and unique development stage, many studies have been undertaken in other countries to better understand the process of initial trust of the local consumers in online shopping. As in Malaysia, studies of such are still at the infant stage, thus this study is in timely need to contribute in meeting the aspiration of the 9th Malaysian Development Plan in becoming a regional ICT hub and in accelerating the growth of online business. This study aims toidentify the factors that significantly contribute to the initial trust amongst Malaysian online shoppers. The determinant of initial trust comprises two interrelated components, i) First Time Experience and ii) Individual Characteristics of the Malaysian online shoppers. The first time experience is defined as a five factor construct comprising Psychological, Risk, Credibility, Environment, and Knowledge whilst the individual characteristics are a four factor construct consisting of Personality, Intention, Brand Consciousness, and Convenience Seeking. The Initial Trust framework for the study is developed through the mixed method approach. The factors are identified based on the outputs from the focus group discussion among selected online shoppers as well as literature on trust in online and online shopping studies. The instrument development followed the eight-step process of instrument development suggested by Churchill (1976). As the focus of this study is to establish the causal relationships between the determinants of initial trust (measures as first time experience and individual characteristics) and initial trust amongst online shoppers, the relationship between first time experience, individual characteristics and initial trust is explored using the structural equation modelling. The major findings of this study indicated that there are six factors that significantly influence the initial trust of online Malaysian consumers which are Psychological, Risk, Credibility, Knowledge, Intention, and Convenience Seeking. The demographic factors do not significantly alter the online shoppers’ perception of their first time experience. This is interesting as the proposed model can be used for all the demographic variables measuring initial trust for future studies. As for the cause effect association between first time experience individual characteristics and initial trust, there are positive causal relationships between first time experience, individual characteristics, and initial trust.